2005
DOI: 10.1111/j.1572-0241.2005.41646.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pancreatitis in Patients on Chronic Peritoneal Dialysis: An Increased Risk?

Abstract: PD is a risk factor for AP. There is no statistical difference in AP-related mortality and morbidity between HD and PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 21 publications
1
26
0
1
Order By: Relevance
“…Several studies confirmed the higher incidence of AP in patients receiving PD, either in comparison to HD patients or in the general populations [3], [4]. For patients receiving PD, it has been hypothesized that both elevated abdominal pressure during PD and a non-physiological composition solution may contribute to premature proteolytic enzymes activation, leading to an AP attack [3].…”
Section: Discussionmentioning
confidence: 92%
“…Several studies confirmed the higher incidence of AP in patients receiving PD, either in comparison to HD patients or in the general populations [3], [4]. For patients receiving PD, it has been hypothesized that both elevated abdominal pressure during PD and a non-physiological composition solution may contribute to premature proteolytic enzymes activation, leading to an AP attack [3].…”
Section: Discussionmentioning
confidence: 92%
“…Pancreatitis is a well-recognized complication of this disease, and its frequency appears to be related to the type of dialysis. In one US study, the incidence of acute pancreatitis was 18.4 per 1000 personyears in patients receiving peritoneal dialysis and 6.5 per 1000 person-years in those receiving hemodialysis [26]. A survey of German patients observed a similar excess in patients receiving peritoneal dialysis [27].…”
Section: Additional Causesmentioning
confidence: 97%
“…6 "Local hypercalcemia" in the pancreas due to calcium in the PD solution has also been postulated. 7 Increase in various gastrointestinal hormones such as cholecystokinin, gastric inhibitory polypeptide, and glucagon in patients with CKD can stimulate hypersecretion of pancreatic enzymes such as trypsin which can contribute to impairment in pancreatic function. 8 There is also this unique situation of coexistence of peritonitis and pancreatitis in patients who are on CAPD.…”
Section: Discussionmentioning
confidence: 99%